Detection possibilities of pore structures: Detektionsmöglichkeiten von Porenstrukturen. Issue 5 (16th October 2017) - Anders, Nicole
Abstract: Autoclaved aerated concrete, hereafter referred to as AAC, is characterized as a building material by its very good thermal insulation. This is achieved by a very high porosity of the microstructure. The size of the pores ranges from millimetres to nanometres and depends on the position as well as on the origin of the pore. These can be differentiated into propellant pores, web pores and intercrystalline or interparticle pores. Because of the broad pore size range, it has not been fully explained until now, which pore sizes significantly affect the building material qualities and to what extent. The overall pore size distribution of AAC can only be detected by a combination of different microstructure analysis methods. For this purpose, nitrogen sorption analysis, mercury intrusion and 3D micro computer tomography were used as an effective combination. Three samples were tested, which show different mineralogical phase compositions because of the differentiation of the formulation. On the basis of these samples and the pore size distribution, which is usually used for the description of the frost and resistance to de‐icing salt of concrete, initial insights into the influence of the respective pore size on the building material properties of AAC could be gained.